2006
DOI: 10.1097/01.nmd.0000243796.60915.9a
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lateral Preference and Peritraumatic Reactions to the World Trade Center Attacks

Abstract: There is evidence that mixed lateral preference is a risk factor for developing more intense posttraumatic stress disorder symptoms. However, no research has examined whether mixed-handed persons experience greater threat of loss of life and physical injury and more intense emotional reactions (terror, helplessness, horror) during peritraumatic exposure. This study compared the intensity of ratings of perceived threat to life and physical injury and emotional reactions among mixed-handed and fully right-handed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…Finally, recent studies suggested that cerebral lateralization is more complex than had been previously recognized (19); hence, mixed handedness might only be a limited index for mixed cerebral lateralization. Nevertheless, our findings were consistent with previous reported studies among diverse populations, including those involving adults and children, as well as persons exposed to both combat and noncombat traumas (1,2,4,5,7). The fact that our national study was consistent with results from smaller local studies, we think, supports the validity of our findings.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, recent studies suggested that cerebral lateralization is more complex than had been previously recognized (19); hence, mixed handedness might only be a limited index for mixed cerebral lateralization. Nevertheless, our findings were consistent with previous reported studies among diverse populations, including those involving adults and children, as well as persons exposed to both combat and noncombat traumas (1,2,4,5,7). The fact that our national study was consistent with results from smaller local studies, we think, supports the validity of our findings.…”
Section: Discussionsupporting
confidence: 94%
“…However, our findings of a relationship between PTSD severity and mixed handedness are in line with previous reports among other diverse populations (Boscarino & Hoffman, 2007;Chemtob et al, 2006;Chemtob & Taylor, 2003;Saltzman et al, 2006;Spivak et al, 1998). The marked differences in the relationship between PTSD symptoms and lateral preference between the groups can imply that moral attitudes might mediate combatant's psychological and organic well-being.…”
Section: Discussionsupporting
confidence: 92%
“…The drug-naive patients reported lower ACE than the drug-treated ones, in agreement with previous reports of increased rates of psychotropic prescriptions in humans exposed to ACE. Left or mixed lateral preference has been consistently associated with greater emotional distress during exposure to traumatic events 31 and with a greater probability to develop posttraumatic stress disorder. Left or mixed lateral preference has been consistently associated with greater emotional distress during exposure to traumatic events 31 and with a greater probability to develop posttraumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%